Convergence and Data Dependency of Normal−S Iterative Method for Discontinuous Operators on Banach Space. (17th February 2018) - Gürsoy, Faik; Khan, Abdul Rahim; Ertürk, Müzeyyen; Karakaya, Vatan
ABSTRACT: We study convergence, rate of convergence and data dependency of normal− S iterative method for a fixed point of a discontinuous operator T on a Banach space. We also prove some Collage type theorems for T . The main aim here is to show that there is a close relationship between the concepts of data dependency of fixed points and the collage theorems and show that the latter provides better estimate. Numerical examples in support of the results obtained are also given.